Latin American homicide - Escaño, Guillermo Jesús (Routledge handbook of homicide studies, 2024)
The urgency for studying Latin America and the Caribbean (LAC) emanates from violence rates that are remarkably higher than in most world regions. Global homicide rates have recently declined. While LAC followed suit, its rates are still comparatively high, and it is home to less than 10% of the global population but about one-third of homicides. The Pan American Health Organization deemed LAC violence the social pandemic of the century in the Americas. Despite its persistent high violence rates, criminologists have only recently begun producing more systematic and empirical analyses in the region. This chapter outlines the demographic characteristics of the region, spatial and temporal variation in homicide rates, some potential structural covariates of homicide rates, and the consequences of violence.